Mohs micrographic surgery for dermatofibrosarcoma protuberans: comparison of frozen and paraffin techniques. (20th August 2018) - Lee, S.H.; Oh, Y.; Nam, K.A.; Oh, B.; Roh, M.R.; Chung, K.Y.
Abstract: Background: Due to the propensity for local recurrence, Mohs micrographic surgery (MMS) has been suggested for the treatment of dermatofibrosarcoma protuberans (DFSP) and it has shown improved clinical outcomes. Recently, some authors suggested that MMS using paraffin‐embedded sections (paraffin MMS) is superior in DFSP treatment compared with the conventional frozen MMS method. However, there have been no studies comparing frozen and paraffin MMS for the treatment of DFSP. Objectives: To compare the outcomes between DFSP patients who underwent frozen MMS and paraffin MMS. Methods: Seventy‐one DFSP patients treated with frozen MMS ( n = 30) or paraffin MMS ( n = 41) from 2003 to 2017 at a single institution were retrospectively reviewed. Recurrence rate and recurrence‐free survival between frozen and paraffin MMS were assessed. Results: During the mean follow‐up duration of 25.4 months, four patients (frozen MMS, n = 1; and paraffin MMS, n = 3) showed recurrence after MMS. Although the local recurrence rate of the frozen MMS group (3.3%) was lower than that of the paraffin MMS group (7.3%), the difference was not statistically significant. In addition, recurrence‐free survival was not significantly different between the two groups ( P = 0.168). Conclusions: Frozen MMS, which has the advantages of shorter surgery time and immediate closure, is as effective as paraffin MMS in the treatment of DFSP.